THE ROLE AND RESPONSIBILITIES OF THE CONTRACTING AGENT UNDER THE TERMS OF LAW NO. 14.133 OF APRIL 1ST, 2021 (CIPEEX, 2024)
LAW NO. 14.133 OF APRIL 1ST, 2021 HAS INTRODUCED NEW FEATURES INTO THE BIDDING PROCEDURES CARRIED OUT BY THE DIRECT AND INDIRECT ADMINISTRATIONS. IN THIS WAY, THE ROLE OF THE CONTRACTING AGENT EMERGES IN THE BIDDING PROCESS, MAKING IT NECESSARY TO ANALYZE THEIR ROLE, AS WELL AS THEIR RESPONSIBILITIES AND THE CIVIL, CRIMINAL, AND ADMINISTRATIVE CONSEQUENCES OF THEIR ACTIONS. THE BIDDING PROCESS IS A FORM OF COMPETITION BETWEEN INDIVIDUALS WHO WANT TO PROVIDE SERVICES, AND SELL OR DISPOSE OF GOODS FOR THE PUBLIC ADMINISTRATION, RESPECTING THE PRINCIPLES OF THE ADMINISTRATION. THIS PROCESS IS A FORMAL ACT, WITH DEFINED RULES AND OBJECTIVES, AIMING TO OBTAIN THE BEST PRICES AND TO ALLOW THE PARTICIPATION OF THE INTEREST PARTIES. THE LAW NO. 14.133/21 CONTAINS NEW TOPICS TO INCREASE TRANSPARENCY IN THE PROCESS OF PUBLIC BIDDING AND CONTRACTING, DISCOURAGING ANY FORM OF CORRUPTION. THESE NEW MECHANISMS ARE A WAY OF MITIGATING POORLY PLANNED CONTRACTS, WHICH CAN DISTURB THE PROCESS IN ITS EFFICIENCY. THE CONTRACTING AGENT IS RESPONSIBLE FOR CONDUCTING THE BIDDING PROCESS, MAKING THE DECISIONS, AND MANAGING OTHER ACTIVITIES NECESSARY FOR THE PROGRESS UNTIL ITS APPROVAL. IT€™S IMPORTANT TO SUMMARIZE THAT THE RELATIONSHIP BETWEEN ADMINISTRATIVE IMPROBITY IS DIRECTLY LINKED TO CORRUPTION, SUCH AS ACTS OF BRIBERY, NEPOTISM AND EXTORTION. THESE ACTS ARE PUNISHABLE IN WAYS THAT AFFECT THE CONTRACTING AGENT€™S CIVIL AND POLITICAL ACTS, AS WELL AS DISMISSAL AND FINE PENALTIES. THE CONTRACTING AGENT IS ESSENTIAL IN THE BIDDING PROCESS, AND HAS A HUGE RESPONSIBILITY IN THEIR ROLE, BY DOING ONLY WHAT IS ALLOWED BY THE LAW.
Keywords: bidding process; contracting agent; responsibility